PENGARUH FAKTOR INTERNAL DAN EKSTERNAL TERHADAP DEVIASI DYNAMIC POSITIONING SYSTEM PADA OPERASI REMOTELY OPERATED VEHICLE DI AHTS OPS AQEELA - Fanny Nurdiansyah, Mario; Agung Istri Sri Wahyuni, Anak; Wani Sihaloho, Otri; Arleiny, Arleiny (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
Position deviations in Dynamic Positioning (DP) systems on offshore support vessels like AHTS OPS Aqeela threaten Remotely Operated Vehicle (ROV) operation safety during subsea inspections. This study analyzes the partial and simultaneous effects of internal factors (engine load, thruster load) and external factors (current speed, wind speed) on DP deviation. Employing a quantitative inferential approach with multiple linear regression, data were sourced from 90 purposive samples of DP View Print records (every 30 minutes over 5 days in May 2025 at Bukit Tua Field). Instruments included Bridgemate MT printouts, analyzed via SPSS for classical assumption tests, t-test, F-test, and R². Results reveal current speed significantly influences deviation positively (t=6.273, p=0.000), while others do not partially; simultaneously, all variables are significant (F=10.341, p=0.000), explaining 32.7% variance. Current speed dominates due to hydrodynamic forces on hull and umbilical, with internal loads acting reactively. Recommendations prioritize current monitoring for enhanced safety.